Fashioning Muslim men: Appraising professional Saudi men's attitudes towards the thobe. Issue 1 (1st September 2019) - DeCoursey, C. A.
The Muslim man's shirt-dress, or thobe, is a popular form of dress in the global Muslim community. Attention to Muslim clothing has most often been to its associated ideology. As a fashionable garment worn across many regions of the world, the thobe has received little attention within the fashion industry or from fashion scholars. This study used Appraisal methods to analyse the subjective attitudes of 79 professional Saudi men in describing their positive and negative views of the thobe. Attitudes were clearly positive overall, realized in engagement clauses reflecting a reserved linguistic style, and showing the collectivist and uncertainty-avoidant social values characteristic of educated Saudi men. The reserved nature of the Saudi male style means that positive results may be read as significantly more positive than subcategory frequencies would otherwise suggest. Frequently realized judgements of social sanction indicate that participants enjoyed the thobe because it allowed them to participate in shared national and religious identities. Frequently realized judgements of social esteem indicate that they find it more practical and comfortable than western wear. Participants identified a variety of elements of design that are desirable and significant to them in a thobe. They distinguished different kinds of thobes based on their social function and context.